Proposta de um sistema automatizado de irrigação por gotejamento utilizando Arduino - CONCEIÇÃO, Yago Gomes da (2019)
This paper addresses the automation concept to produce a system that controls the irrigation of a given crop by making use of concepts and technologies available to improve product quality and reduce the unnecessary consumption of water, thus facilitating the cultivation and increasing profit on cultivation. To realize this project we used the Arduino UNO board that plays the role of process controller, relizando treating provenites signals from the external environment and sending control agreements with these signals. A humidity sensor implanted in the planting area is the monitoring of the soil according to a comparison between the ideal humidity and average humidity, makes the drive solenoid valves that allow irrigation. Once the soil moisture reaches the reference Arduino interrupts irrigation causing the closing of the valves. The differential of this application is to study the necessity of adapting the code for each type of crop. The system also provides, through an LCD screen monitoring of soil moisture in real time as well as the status of solenoid valves. The practical study was conducted in a plantation of açaí seedlings.